Against Better Knowledge: The Magical Force of Amodal Volume Completion. (December 2013) - Ekroll, Vebjørn; Sayim, Bilge; Wagemans, Johan
In a popular magic routine known as "multiplying billiard balls", magicians fool their audience by using an empty shell that the audience believes to be a complete ball. Here, we present some observations suggesting that the spectators do not merely entertain the intellectual belief that the balls are all solid, but rather automatically and immediately perceive them as such. Our observations demonstrate the surprising potency and genuinely perceptual origin of amodal volume completion.